Mechanical properties of polypropylene blends with banana fibre / Nur Ainni Md Shariff - Md Shariff, Nur Ainni (2008)
Fiber Reinforced Polymer (FRP) composites is defined as a polymer matrix (thermoset or thermoplastic) combined with a fiber or other reinforcing material to provide discernable reinforcing function in one or more directions. The benefits which is including light weight, directional strength and other properties makes the FRP composites famous in the automotive, building and plastic industries. PP has been widely used in plastic industry and the price has been increase. The banana plant or Musaceae's fibers are usually for high quality textiles. The banana stems fiber is mix with PP resins in order to reduce cost and to create new types of composites. The physical testing is carried out to know and compare within all these composites. By comparing all composites, it showed that composites 3 percent of banana fibers and 97 percent of PP resins will gives good physical properties compares to others mixes.